Analisis Teknik Dasar Bermain Futsal Timnas Putri Indonesia Pada Piala AFC Woman’s Championship Tahun 2018 - Rike Ditya Agischa; Heri Wahyudi (Indonesian Journal of Kinanthropology (IJOK), 2022)
Background: Basic technique is a skill and a person's ability to move effectively with one goal. The success of carrying out these basic techniques can be seen in the match between the Indonesian Women's Futsal National Team against Macau in the AFC Women's Futsal Championship Cup in Thailand in 2018. The purpose of the research based on this background is to find out (1) Describe the basic playing techniques used in the AFC Women's Futsal Cup match. Championship in 2018 (2) Describes the number of basic techniques used in percent. Methods: By using this type of quantitative research descriptive method, Results: The research results were found as follows: there were four basic techniques used by the Women's National Futsal Team in the 2018 AFC Women's Championship trophy during the match, namely passing, dribbling, shooting, and control Conclusions: The most widely used basic technique is control as much as 41%, passing and dribbling techniques have a fairly thin difference as much as 4% with 28% passing and 24% dribbling. While the basic shooting technique used at least 7%. The details of the basic techniques when viewed in terms of numbers are 1) Passing as many as 371 with 329 inner passes and 42 outer passes. 2) 319 dribbling with 148 first and 171 second. 3) Shooting 93 with 63 live balls and 30 dead balls. 4) Control 540 with the first 281 and 259 second.